ENT 530 Social Media Portfolio / Hanisah Saahal - Saahal, Hanisah (2019)
Product of Popiah Seaweed has been widened nowadays. It is because of the dumpling skin with the seaweed itself. It has a crunchy taste and delicious. It is very affordable price and all aged are able to buy it. Targeting and segmenting to whomever likes seaweed and to whose like to have their snacks during all time.